Celebrating geography's place in an inclusive and collaborative Anthropo(s)cene. (November 2015) - Leichenko, Robin; Mahecha, Ana
The widespread recognition that humans have become geological agents offers an opportune moment for reflection on how geographers are contributing to the rapidly growing and highly interdisciplinary field of Anthropocene research. In this commentary, we situate geographers and geographic concepts as playing pivotal roles in Anthropocene work both in the past and today. We highlight the inclusive, collaborative and interdisciplinary nature of the work and the openings that it offers for rethinking knowledge production. Through our comments, we hope to convey and cultivate an Anthropo(s)cene that is inclusive, collaborative and welcoming of a broad range of scholarship in human geography.